PENGUJIAN BEBERAPA KOMBINASI MEDIUM TANAM DENGAN PEMBERIAN BERBAGAI VOLUME AIR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMANPAKCHOY (Brassica chinensis L.) YANG DIBUDIDAYAKAN SECARA VERTIKULTUR - Sartika Eka Putri; Ardian '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Pakchoy plants (Brassica chinensis L. ) is a plant that much in demand by the public because of high nutritional content. The limited agricultural land currently caused pakchoy cultivation declined, one of the ways that can be used to overcome this problem is to utilize the limited land by verticulture manner. Nutrients and water is a very important factor for plant growth of pakchoy, thus providing a variety of growing media and the provision of water can improve plant growth and production. Research has been conducted on the home screen Technical Services Unit Faculty of Agriculture, University of Riau from September to November 2014. The research conducted experimentally using Completely Randomized Design (CRD) consist 2 factors: embedding medium and the volume of water. The first factor is the growing medium consisting of three types of medium, M1=inceptisol soil, M2= 75% Inceptisol  and 25% cocopeat, M3= 75% inceptisol and 25% ash sawdust and the second factor consists of 3 volumes of water that V1=100 ml/day, V2=200 ml/day, V3= 300 ml/day. Parameters measured were plant height, number of leaves, leaf area, fresh weight, weight suitable for consumption and root volume. The results showed that the volume of water with planting medium ash sawdust effect on growth and yield of pakchoy. Provision of water volume of 200 ml and the embedding medium ash sawdust with vertikultur system gives the best effect on plant height, number of leaves, leaf area, plant fresh weight, fresh weight of plants suitable for consumption, and root volume.   Keyword: pakchoy, medium, water volume, verticulture